2021
DOI: 10.3390/genes12020128
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Statistical Phasing Framework for the Analysis of Forensic Mitochondrial DNA Mixtures

Abstract: Despite the benefits of quantitative data generated by massively parallel sequencing, resolving mitotypes from mixtures occurring in certain ratios remains challenging. In this study, a bioinformatic mixture deconvolution method centered on population-based phasing was developed and validated. The method was first tested on 270 in silico two-person mixtures varying in mixture proportions. An assortment of external reference panels containing information on haplotypic variation (from similar and different haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
(158 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, confirmation testing using an enrichment method such as long-range amplification to minimize NUMT interference was not possible for the SweGen dataset. In these cases, the mtDNA haplogroup of the major and minor haplotypes may provide some guidance to the source of the mixture (Table S1) [35,36], and potentially assist in the identification of NUMTs [37]. However, phylogenetic analysis does not eliminate the possibility that the mixture results from a mega-NUMT from a "modern" mtDNA haplogroup, as was detected in Lutz-Bonengel et al [6].…”
Section: Excluded Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, confirmation testing using an enrichment method such as long-range amplification to minimize NUMT interference was not possible for the SweGen dataset. In these cases, the mtDNA haplogroup of the major and minor haplotypes may provide some guidance to the source of the mixture (Table S1) [35,36], and potentially assist in the identification of NUMTs [37]. However, phylogenetic analysis does not eliminate the possibility that the mixture results from a mega-NUMT from a "modern" mtDNA haplogroup, as was detected in Lutz-Bonengel et al [6].…”
Section: Excluded Samplesmentioning
confidence: 99%
“…Classification of PHPs or NUMTs is further complicated, as np 16093 is a known heteroplasmic hotspot [39] with variations observed across sample types [44]. Cihlar et al [26] have previously discussed the difficulty of distinguishing authentic heteroplasmy at np 16093 from NUMT variants in small amplicon NGS data, and suggested the use of phylogenetic information as a possible solution [37]. Another, more conservative option for a hotspot like np 16093 could be to ignore the position in all data interpretations due to its variability and susceptibility to NUMT interference.…”
Section: Comparison With High-quality Mitogenome Datasetsmentioning
confidence: 99%
“…For example, a population study to assess of the efficacy of an mtMPS approach in forensic laboratories (Avila et al, 2019), concluded that mtMPS analysis should be the method of choice. Other studies have illustrated that mtMPS is a powerful means of deconvoluting two or three‐person mixtures (Smart et al, 2021; Churchill et al, 2018; Vohr et al, 2017; Kim et al, 2015).…”
Section: Massively Parallel Sequencingmentioning
confidence: 99%
“…MPS can detect and resolve mixed mtDNA sequences of low‐level minor variants providing a powerful means of deconvoluting two and three‐person mixtures (Smart et al, 2021; Nakanishi et al, 2020; Churchill et al, 2018; Vohr et al, 2017; Kim et al, 2015), whereas STS cannot achieve this feat. Specifically, MPS can detect and resolve mixtures, including heteroplasmy, at threshold levels as low as 1–2%, whereas STS can only detect mixed sites when the minor variant reaches 5–10%, and in some cases not until 20% depending on the noise encountered in the data (González et al, 2020; Holland et al, 2011, 2018, 2019; Irwin et al, 2009; Just, Irwin, et al, 2015; Kloss‐Brandstätter et al, 2015; McElhoe et al, 2014; Melton, 2004; Parson et al, 2015).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…In this study we developed and evaluated a strategy to deconvolute mtDNA mixtures using phylogenetic principles. Earlier attempts to separate human mtDNA mixtures applied physical methods, such as denaturing high-performance liquid chromatography [6] , [18] , base composition profiling using mass spectrometry [12] , quantitative data in a statistical framework [9] and MPS-based data [5] , [13] , [21] with a continuous statistical phasing framework [28] . While some of these strategies have proven useful, there is still a lack of technology-agnostic, non-quantitative and easy to use mtDNA mixture deconvolution tools that provide traceable splittings on any kind of sequencing data (Sanger and MPS).…”
Section: Introductionmentioning
confidence: 99%